POLISH SOCIAL WORKERS, POSITIVE ORIENTATION AND THEIR READINESS TO CHANGE - Czechowska-Bieluga, Marta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The author has researched the relation between social workers’ positive orientation and their level of readiness to change. The study included 103 Polish social workers from social welfare centres in Lublin Province, which is classified as one of the poorest administrative regions in the EU. Random sampling of cases for the study was used. Lublin, Poland, is a city in which the prevalence of social assistance provided by social workers is on an average level compared to the entire country. The aim of the presented studies was to verify the correlation of the positive orientation of social workers employed in Lublin, Poland, with their readiness for change. The results of the research have revealed that most subjects presented a low level of all the traits which were analysed and which define the readiness to change. The study also revealed statistically significant correlation between the positive orientation and the readiness to change in general and in the following traits: confidence, drive, optimism, and resourcefulness.